Genomic Diversity and Virulence Potential of ESBL- and AmpC-β-Lactamase-Producing Escherichia coli Strains From Healthy Food Animals Across Europe - Ewers, Christa; de Jong, Anno; Prenger-Berninghoff, Ellen; El Garch, Farid; Leidner, Ursula; Tiwari, Sumeet K.; Semmler, Torsten (Frontiers in Microbiology, 2021)
The role of livestock animals as a putative source of ESBL/pAmpC E. coli for humans is a central issue of research. In a large-scale pan-European surveillance, 993 commensal Escherichia spp. isolates were recovered from randomly collected fecal samples of healthy cattle, pigs and chickens in various abattoirs. One-hundred Escherichia spp. isolates (0.5% from cattle, 1.3% pigs, 8.0% chickens) fulfilled the criteria for cefotaxime and ceftazidime non-wildtype (EUCAST). In silico screening of WGS data of 99 isolates (98 E. coli and 1 E. fergusonii) revealed blaSHV-12 (32.3%), blaCTX-M-1 (24.2%), and blaCMY-2 (22.2%) as predominant ESBL/pAmpC types. Other types were blaSHV-2 (1.0%), blaCTX-M-2/-14/-15 (1.0/6.1/1.0%), and blaTEM-52 (5.1%). Six isolates revealed AmpC-promoter mutations (position -42 (C>T) and one carried mcr-1. The majority (91.3%) of ESBL/pAmpC genes were located on plasmids. SHV-12 was mainly (50%) encoded on IncI1α plasmids (pST-3/-26/-95), followed by IncX3 (12.5%) and IncK2 (3.1%). The blaTEM-52 genes were located on IncI1α-pST-36 (60%) and IncX1 plasmids (20%). The dominant plasmid lineage among CTX-M-1 isolates was IncI1α (pST-3/-295/-317) (87.5%), followed by IncN-pST-1 (8.3%). CMY-2 was mostly identified on IncI1α (pST-12/-2) (54.5%) and IncK2 (31.8%) plasmids. Several plasmids revealed high similarity to published plasmids from human and animal Enterobacteriaceae. The isolates were assigned to phylogroups A/C (34.7/7.1%), B1 (27.6%), B2 (3.1%), D/F (9.2/10.2%), E (5.1%) and to E. clades (3.0%). With 51 known and 2 novel MLST types, a wide variety of STs was found, including STs previously observed in human isolates (ST10/38/117/131/648). ESBL/AmpC types or STs were rarely correlated with the geographic origin of the isolates or animal species. Virulence gene typing identified extraintestinal pathogenic E. coli (ExPEC; 2.0%), avian pathogenic E. coli (APEC; 51.5%), and atypical enteropathogenic E. coli (EPEC; 6.1%). In conclusion, the high diversity of STs and phylogenetic groups provides hardly any hint for clonal spread of single lineages but hints towards the dissemination of cephalosporin resistance genes in livestock via distinct, globally successful plasmid lineages. Even though a number of isolates could not be assigned to a distinct pathotype, our finding of combined multidrug-resistance and virulence in this facultative pathogen should be considered an additional threat to public health.